PENGARUH KUALITAS LAYANAN DAN CITRA PERUSAHAAN TERHADAP KEPUASAN PELANGGAN E-COMMERCE BLIBLI DI KOTA BEKASI - Dhina Nur Fitriana; Nino Nopriandi (Jurnal Ekonomi dan Industri, 2023)
Purpose to analyze the effect of service quality and corporate image on customer satisfaction of Blibli E-Commerce in Bekasi City. The research method uses descriptive qualitative and quantitative analysis. The population in this study are customers of E-Commerce companies in Bekasi City, whose numbers are unknown. The sampling technique used purposive sampling with the criteria of being 17 years old and having used E-Commerce for 1 year. The analytical method used is partially and simultaneous linear regression. The results of the study show that in partially service quality and corporate image have a significant effect on E-Commerce customer Blibli satisfaction in Bekasi City. Taken simultaneous, service quality and corporate image have a positive and significant effect on E-Commerce Blibli customer satisfaction in Bekasi City.